2015
DOI: 10.1016/j.rfe.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Trading behavior in S&P 500 index futures

Abstract: This article examines the determinants of trading decisions and the performance of trader types, in the context of the E‐Mini S&P 500 futures and S&P 500 futures markets. Speculators and small traders tend to follow positive feedback strategies while hedgers dynamically adjust positions in response to market returns. Such strategies apparently reverse during the 2008–09 financial crisis. Investor sentiment and market volatility play an important role in determining the net trading position of traders across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…, 2007; Kurov, 2008; Salm and Schuppli, 2010; Antoniou et al. , 2011; Lai and Wang, 2014, 2015; Smales, 2016; Chen and Yang, 2021) confirming empirically the significance of (predominantly, positive) feedback trading in that segment [83]. At the macro level, positive feedback traders often appear more active in index futures during market slumps (likely due to index futures being utilized for portfolio insurance – Salm and Schuppli, 2010; Antoniou et al.…”
Section: Empirical Evidencementioning
confidence: 59%
See 3 more Smart Citations
“…, 2007; Kurov, 2008; Salm and Schuppli, 2010; Antoniou et al. , 2011; Lai and Wang, 2014, 2015; Smales, 2016; Chen and Yang, 2021) confirming empirically the significance of (predominantly, positive) feedback trading in that segment [83]. At the macro level, positive feedback traders often appear more active in index futures during market slumps (likely due to index futures being utilized for portfolio insurance – Salm and Schuppli, 2010; Antoniou et al.…”
Section: Empirical Evidencementioning
confidence: 59%
“…The bulk of research on feedback trading in derivatives' markets pertains to index futures contracts [82], with a large number of studies (Wang, 2002(Wang, , 2003Ghysels and Seon, 2005;Cheng et al, 2007;Kurov, 2008;Salm and Schuppli, 2010;Antoniou et al, 2011;Wang, 2014, 2015;Smales, 2016;Chen and Yang, 2021) confirming empirically the significance of (predominantly, positive) feedback trading in that segment [83]. At the macro level, positive feedback traders often appear more active in index futures during market slumps (likely due to index futures being utilized for portfolio insurance -Salm and Schuppli, 2010; Antoniou et al, 2011) [84] and extrapolate from horizons of several days ("long memory"; Antoniou et al, 2011).…”
Section: Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hamid and Iqbal [ 12 ] used the neural network to improve the accuracy of prediction of the volatility of S&P 500 stock index futures. By studying the trading behavior of S&P 500 stock index futures, Smales [ 13 ] found that after the 2008 financial crisis, investors abandoned the previously widely adopted positive feedback trading method and switched to the investment strategy with market volatility and investor sentiment as the main reference standard. China, which has the world’s second largest economy, has been developing stock index futures for a relatively short time, but it is still widely followed by financial market participants.…”
Section: Introductionmentioning
confidence: 99%